Biologi Populasi Rajungan (Portunus Pelagicus) dan Karakteristik Lingkungan Habitat Esensialnya Sebagai Upaya Awal Perlindungan di Lampung Timur - Rahmat Kurnia; Mennofatria Boer; . Zairion (Institut Pertanian Bogor, 2014)
There are several option management measures in preventing sustainability stock of the blue swimming crab (Portunus pelagicus), i.e., nursery ground conservation. Thus, the objective of this study was to analyses habitat characteristic and its population biology in the PGN marine embayment of Labuhan Maringgai, as one among crab habitat essential in East Lampung coastal water. The potential nursery ground conservation was assessed by habitat suitability index, carrying capacity, distribution and abundance as well as crabs size. The result shows that environmental condition was still suitable, even though the habitat carrying capacity tend to degraded by an increasing of turbidity and sedimentation at the embayment mouth. The crabs captured were also not representing of peak abundance season and recruitment during sampling period, while those crab size almost 100% under Lm50. The strategic management directive is required to control in utilization of crab’s essential habitat, including crab fishing by any fishing gear resulted undersize captured crabs. Meanwhile, to propose habitat essential conservation might need more consideration and comprehensive study, including social economic and cultural aspects and co-management approach may be required in management measure applied.